Values clarification workshops to improve abortion knowledge, attitudes and intentions: a pre-post assessment in 12 countries - Katherine L. Turner; Erin Pearson; Allison George; Kathryn L. Andersen (BMC, 2018)
Abstract Background Women's access to abortion care is often denied or hampered due to a range of barriers, many of which are rooted in abortion stigma. Abortion values clarification and attitude transformation (VCAT) workshops are conducted with abortion providers, trainers, and policymakers and other stakeholders to mitigate the effects of abortion stigma and increase provision of and access to abortion care. This study assesses changes in knowledge, attitudes, and behavioral intentions of VCAT workshop participants. Methods Pre- and post-workshop surveys from 43 VCAT workshops conducted in 12 countries in Asia, Africa, and Latin America between 2006 and 2011 were analyzed to assess changes in three domains: knowledge, attitudes and behavioral intentions related to abortion care. A score was created for each domain (range: 0-100), and paired t-tests or Wilcoxon matched-pairs signed-ranks tests were used to test for significant differences between the pre- and post-workshop scores overall and by region and participant type (providers, trainers, and policymakers/other stakeholders). We also assessed changes in pre- and post-workshop scores for participants with the lowest knowledge and negative attitudes on the pre-workshop survey. Results Overall, the mean knowledge score increased significantly from 49.0 to 67.1 (p < 0.001) out of a total possible score of 100. Attitudes and behavioral intentions showed more modest, but still statistically significant improvements between the pre- and post-workshop surveys. The mean attitudes score increased from 78.2 to 80.9 (p < 0.001), and the mean behavioral intentions score rose from 82.2 to 85.4 (p = 0.03). Among participants with negative attitudes pre-workshop, most shifted to positive attitudes on the post-workshop survey, ranging from 35.2% who switched to supporting unrestricted access to second-trimester abortion to 90.9% who switched to feeling comfortable working to increase access to contraceptive services in their country. Participants who began the workshop with the lowest level of knowledge experienced the greatest increase in mean knowledge score from 20.0 to 55.0 between pre- and post-workshop surveys (p < 0.001). Conclusions VCAT workshop participants demonstrated improvements in knowledge, attitudes, and behavioral intentions related to abortion care. Participants who entered the workshops with the lowest levels of knowledge and negative attitudes had the greatest gains in these domains.